ANALYZING THE POLICY ON EDUCATION VIOLATIONS AND PENALTIES IN THE PERSPECTIVE OF ISLAMIC EDUCATION IN THE MINISTRY OF RELIGION KABUPATEN KAMPAR - Ismail Ismail (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This study aimed to reveal the policies of educational institutions towards violations and penalties in the perspective of Islamic education in Indonesia. This research was conducted at Madrasah Negeri in Kabupaten Kampar from June 2020 - October 2020. The population in this study was all teachers teaching at Madrasah Negeri. This research utilized observation, in-depth interviews, and documentation repeatedly to collect the data. The results showed that Law Number 20 of 2003, there were three types of violations committed by teachers in educational institutions: 1) fake degrees, 2) plagiarisms and 3) certificates issued by unformal institutions. Meanwhile, the violations committed by students were the truancy during school hours, smoking, destroying school facilities and infrastructure, and fighting during school hours.